Design of Web-Based Real Count Information System for Village Head Election: Perancangan sistem informasi real count pemilihan kepala dusun berbasis web - Meiliza Nurfayani; Raimon Efendi; Wahyu Prima (Perkumpulan Doktor Indonesia Maju (PDIM), 2023)
The election of village heads is an integral part of the democratic process at the local level. However, there are often challenges in the vote-counting process that can impede the smooth implementation of village head elections. This article proposes designing a web-based Real Count information system for village head elections in the Tanah Sepenggal Lintas District. The main issue identified is the delay in vote counting, affecting the speed of the official announcement of results by the General Election Commission (KPU). The research methodology includes problem identification, analysis, goal setting, literature review, data collection, system analysis, system design, testing, and implementation. The resulting system aims to expedite and enhance the accuracy of vote counting using web-based technology, notably PHP and MySQL. This approach is expected to address traditional challenges in vote counting and provide quick and efficient information on the results of village head elections. The research findings indicate that the designed Real Count information system successfully improves the efficiency of vote counting, reduces the waiting time for official announcements, and provides transparent information on election results. Implementing this system is expected to positively enhance the integrity and speed of village head elections at the local level.